2016
DOI: 10.1093/ndt/gfw070
|View full text |Cite
|
Sign up to set email alerts
|

Renal biopsy in patients with diabetes: a pooled meta-analysis of 48 studies

Abstract: Background. The utility of renal biopsy in patients with diabetes is highly debated. Diabetics with rapidly worsening renal disease are often 'clinically' labelled as having diabetic nephropathy (DN), whereas, in many cases, they are rather developing a nondiabetic renal disease (NDRD) or mixed forms (DN þ NDRD). Methods. We performed a systematic search for studies on patients with diabetes with data on the frequency of DN, NDRD and mixed forms, and assessed the positive predictive values (PPVs) and odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
131
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(157 citation statements)
references
References 53 publications
10
131
0
2
Order By: Relevance
“…The results showed that a duration of diabetes ≤6 years was an independent predictor of NDRD, with a PPV of 77.7%. These findings are similar to some of previous studies, whereas there are also some studies that fail to find out a significant association between short duration of diabetes and NDRD …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results showed that a duration of diabetes ≤6 years was an independent predictor of NDRD, with a PPV of 77.7%. These findings are similar to some of previous studies, whereas there are also some studies that fail to find out a significant association between short duration of diabetes and NDRD …”
Section: Discussionsupporting
confidence: 92%
“…This may be explained by the very low proportion of MIX groups in their cohort (2/113). However, we and other researchers have revealed a certain proportion of patients with MIX lesions, varying from 4% to 45.5% . Therefore, we further validated the practicability of the NDRD score in the overall population involving the MIX group.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The most frequently seen NDKD types were, IgA nephropathy in 16 studies, MN in 9 studies, FSGS in 6 studies and TIN in 4 studies. Compared to studies from Europe and the United States, in the studies from Asia, IgA nephropathy was the most frequently seen condition, while in the European studies the most frequently seen NDKD was FSGS [23]. In a retrospective study including 620 patients performed in the United States, Sharma et al reported DKD, NDKD and DKD+NDKD prevalence as 37%, 36% and 27%, respectively.…”
Section: Discussionmentioning
confidence: 99%